Entrepreneurial behaviour of family firms perspectives on emerging economies - Krasniqi, Besnik A. (Entrepreneurial behaviour series, 2025)
Offering perspectives on the entrepreneurial behaviour of family businesses in emerging economies, the chapters collected here present a systematic analysis focusing on gender, culture, policy, issues of succession, growth and economic impact